The Future of Work and the Evolving Role of Career Counseling: Preparing Gen Z for the Gig Economy and the Age of Automation. - Endro Baruno, Yosep Heristyo; Maertias, Maertias; Razak, Faisal (International Journal of Research in Counseling, 2024)
This article explores the evolving landscape of work that Generation Z is encountering, with an emphasis on the essential role of career counseling in equipping them for the gig economy and the age of automation. As technological advancements and shifts in labor market dynamics reshape traditional employment models, young job seekers face unique challenges that require innovative strategies for career success. The article employs a research-based approach to examine the key skills necessary for navigating this new work environment, the transformations in work relationships, and the critical function of career counselors in providing pertinent guidance and support. Moreover, it highlights the significance of developing both soft skills—such as adaptability, communication, and problem-solving—and technical skills relevant to emerging industries. The article posits that career counseling not only serves as an important resource for Generation Z in identifying and pursuing job opportunities but also plays a pivotal role in fostering resilience and adaptability in a rapidly changing job market. By addressing the evolving expectations of employers and the impact of automation on job availability, this article aims to provide insights into how career counseling can effectively prepare Generation Z for the future of work.